The effectiveness of the rhythm of alliteration in the poetry of Abu Tammam (231 H) (Journal of Hama University, 2026)
The research seeks to study the effectiveness of the rhythm of alliteration in Abu Tammam’s poetry through a semantic study. Therefore, the research begins with an introduction that includes a discussion of the meaning of the term, then it follows up with a study of the contrast in two aspects: the contrast – perfect parallelism, the contrast – incomplete parallelism.The Keywords:  Abu Tammam, contrast, rhythm, meaning, coherence.
Keywords: The Keywords: Abu Tammam, contrast, rhythm, meaning, coherence.